Risk Factors for Breast Cancer at Undata Regional General Hospital, Central Sulawesi Province - Andi Zuhra Ibrahim; Rajindra Rajindra; Zhanaz Tasya (PT. Anagata Sembagi Education, 2026)
Breast cancer is one of the most common cancers among women and a growing public health problem, including at Undata Regional General Hospital, Central Sulawesi, where inpatient cases rose from 38 in 2022 to 144 by September 2025. This study aimed to analyze the risk factors associated with breast cancer at Undata Hospital. This is a quantitative study with a case-control design involving 104 respondents (52 cases and 52 controls) selected through purposive sampling. The variables were studied menarche, family history, lactation history, hormonal contraceptive use, and age at first childbirth. Data were analyzed using the Odds Ratio (OR) test in bivariate analysis and multiple logistic regression in multivariate analysis. The results showed that all variables were significantly associated with breast cancer after adjustment: early menarche <12 years (AOR=8.942; 95% CI=1.963–40.740), family history (AOR=13.753; 95% CI=2.973–63.629), lactation duration <12 months (AOR=14.024; 95% CI=4.010–49.045), hormonal contraceptive use ≥5 years (AOR=3.226; 95% CI=1.035–10.060), and age at first childbirth ≥30 years (AOR=9.830; 95% CI=1.703–56.745). The most dominant factor was a lactation duration of less than 12 months. Breast cancer incidence is influenced by an interrelated combination of hormonal, reproductive, and genetic factors, highlighting the need for stronger health promotion, risk-factor education, hormonal contraceptive counseling, and early-detection programs.